Carbon footprint comparative analysis for existing and promising thermal power plants - Rogalev, N.D; Rogalev, A.N; Kindra, V.O; Zlyvko, O.V.; Bryzgunov, P.A. (Karagandy University of the name of acad. E.A. Buketov, 2022)
The power production industry is the main greenhouse gas emitter that makes its contribution to global warming. The greenhouse gas emission takes place in fuel production, transportation, and combustion. A prospective method for emission mitigation is the transition to organic fuel-burning facilities with small emissions by capturing carbon dioxide. Power consumption on the carbon dioxide capture remarkably reduces the efficiency of these facilities, which leads to increasing of fuel consumption and greenhouse gas emission because of the larger fuel production and transportation. Based on the material balance method, taking into account system effect of changes in efficiency and amount of fuel consumed, the paper estimated the carbon footprint over a twenty-year lifecycle for following thermal power plants types: combined cycle and oxy-fuel combustion plants for both natural gas and coal with internal gasification. It is shown that the transition to oxygen-fuel plants can reduce the carbon footprint near 90% for natural gas and near 75% for coal. The study also demonstrates the positive effect of carbon capture and storage system implementation for reducing carbon footprint near 75% for natural gas and near 70% for coal.
Keywords: carbon footprint; thermal power plant; combined cycle facility; oxy-fuel cycle; organic fuel; coal gasification